Caracterização do pescador e da frota pesqueira comercial de Manoel Urbano e Sena Madureira (AC) e Boca do Acre (AM) - ALMEIDA, Oriana Trindade de (2013)
Several studies about the ﬁ shing sector have been carried on in the Amazon, however, the majority of these studies are concentrated on regions near the Amazon river bank and its delta. This work has the objective to characterize the Purus commercial ﬁshing ﬂeet and the ﬁsher in three counties: Manoel Urbano and Sena Madureira in the Brazilian state of Acre (AC) and Boca do Acre, in Amazonas (AM).We estimate the ﬁsheries production and income. The results show that in Manoel Urbano (AC) lake ﬁsheries predominate while in Sena Madureira (AC), the diversity in ﬁshing places are lager with ﬁshers using lakes, river and creeks. In Boca do Acre (AM), the largest among the three cities, the most important ﬁshing plots are Pauini and Labrea areas. In relation to boats, Manoel Urbano ﬁshers use only canoes with most of it motorized. In Boca do Acre, ﬁ sheries are practiced mainly in boat. In relation to ﬁshing trip costs the results showed that variable costs are the main costs for canoes (63% of total income) and boats (73% of total income). The analyses showed also that motorized canoes have larger productive capacity per unit of effort (CPUE) in relation to boats.